Membongkar Wacana Tafsir Radikalisme dan Terorisme: Analisis Kritis atas Ideologi Radikal - Priatna Agus Setiawan (La-Tahzan: Jurnal Pendidikan Islam, 2025)
Religious-based radicalism and terrorism are complex global issues where religious interpretation plays an important role in shaping the mindset and actions of religious adherents. Although interpretation functions to understand Islamic teachings in a social, political, and cultural context, in some cases, it is used to justify violence. This study examines the relationship between religious interpretation and radicalism and offers a critique of interpretation methods that tend to support extreme ideologies. Through an analysis of verses from the Qur'an, such as QS. Al-Baqarah: 190-193, this study shows that erroneous understanding can lead to justification for violent acts, as in the case of terrorist groups. Maudhu'i's interpretation is proposed as a more contextual approach to prevent the misuse of the meaning of religious verses. The results of this study confirm that interpretation-based radicalism not only impacts individuals, but also threatens social stability and global security. Therefore, preventing radicalism requires a multidisciplinary approach that includes education, interfaith dialogue, and cooperation between the government, society, and international organizations. Deradicalization efforts and the dissemination of more inclusive religious interpretations are strategic steps in maintaining peace and reducing the spread of extreme ideologies.